Pendampingan Pengelolaan Keuangan Digital Melalui Sosialisasi dan Praktik Penerapan Aplikasi SEPRAN Pada Pelaku UMKM Desa Prima Bumijo - Ayu Puspitha; Zaenal Wafa (LPPI UMN AL WASHLIYAH, 2025)
This community engagement program on digital financial management assistance through socialization and hands-on implementation of the SEPRAN application for MSME actors in Desa Prima Bumijo was carried out to address the issues of low financial literacy and the suboptimal practice of financial record-keeping. The program aimed to improve participants’ understanding of accurate transaction recording and their skills in operating digital financial applications. The methods consisted of socialization, training, and direct practice in using the SEPRAN application, involving 25 MSME actors as program subjects. Data were collected through observation and simple questionnaires to assess participants’ comprehension and competency before and after the intervention. The results showed an improvement in participants’ knowledge of digital financial management and their skills in using the application, including income and expense recording, and generating simple reports. Participants also demonstrated positive changes in daily transaction recording habits. The program concluded that SEPRAN-based digital financial management assistance effectively supports MSMEs in improving the quality of their financial administration. Further programs are recommended to enhance application utilization consistency and provide ongoing technical support.